Attention impairment in motor functional neurological disorders: a neuropsychological study - Věchetová, Gabriela; Nikolai, Tomáš; Slovák, Matěj; Forejtová, Zuzana; Vranka, Marek; Straková, Eva; Teodoro, Tiago; Růžička, Evžen; Edwards, Mark J; Serranová, Tereza (Journal of neurology, 2022)
OBJECTIVE: Our objective was to assess cognitive functioning across multiple cognitive domains using a standardised neuropsychological battery in patients with motor functional neurological disorders (mFND). METHODS: Thirty patients with clinically established mFND and 30 age-, sex- and education-matched control subjects underwent a thorough neuropsychological assessment evaluating (1) attention including processing speed, (2) executive functions including working memory, (3) short-term memory, (4) speech and language and (5) visuospatial functions. Performance validity tests (PVT) and self-report measures of depression, anxiety and cognitive complaints were included in the assessment. Only patients with valid test performance were included in the analysis. RESULTS: Three patients scored below the cut-off scores in PVT. Patients performed significantly worse than controls in the following areas: (1) the attention domain which included a slow processing speed (p = 0.005, Cohen's d = 0.89), (2) executive functions (p = 0.01, Cohen's d = 0.88) and (3) speech and language domains (p = 0.025, Cohen's d = 0.77). Patients with mFND showed greater intra-individual variability in cognitive performance (p = 0.005, Cohen's d = 0.94). Cognitive impairments were independent of depressive symptoms, which were higher in mFND patients. CONCLUSION: This study revealed both subjective and objective cognitive impairment in patients with mFND. The neuropsychological profile in mFND was characterised primarily by attentional impairment including a slow processing speed and a high intra-individual variability in cognitive performance. Cognitive impairment was associated with a valid test performance, highlighting that the deficits observed were not likely to be explained by a lack of effort in the patient group. Attention is considered to play a key role in mFND pathophysiology, and the results suggest that such impairments are objectively measurable.
Keywords: Humans; neuropsychologické testy; Attention; kognice; Conversion Disorder; lidé; Cognitive functions; exekutivní funkce; Performance validity; konverzní poruchy; Cognition Disorders; Neuropsychological Tests; Motor functional neurological disorders; Cognitive Dysfunction; Neuropsychological profile; kognitivní poruchy; Executive Function; Cognition; kognitivní dysfunkce; pozornost